Structure determination and optical properties of CsSm(PO3)4. (March 2015) - Ben Hassen, N.; Ferhi, M.; Horchani-Naifer, K.; Férid, M.
Graphical abstract: Projection of the CsSm(PO3 )4 structure viewing along the a axis. Highlights: Single crystal of a new polyphosphate CsSm(PO3 )4 has been synthesized. The obtained compound has been characterized by several techniques. The crystal structure of CsSm(PO3 )4 has been resolved. Spectroscopic properties of Sm 3+ in CsSm(PO3 )4 have been performed. Abstract: A new alkali metal-rare earth polyphosphate CsSm(PO3 )4 has been synthesized by flux method. The obtained compound has been characterized by means of single crystal X-ray diffraction, Fourier transform infrared (FTIR) and Raman scattering spectroscopies. It crystallizes in the monoclinic space group P21 /n with the following unit-cell parameters: a  = 10.382(2), b  = 8.978(6), c  = 11.205(4) Å, β  = 106.398(3)° and Z  = 4. The structure of CsSm(PO3 )4 is an infinite three-dimensional framework made up of double spiral (PO3 ) n chains linked with neighboring SmO8 and CsO11 polyhedra. Spectroscopic properties of Sm 3+ in this new compound including excitation, emission, and kinetic measurement have been performed. The emission spectrum shows four transitions characteristics of Sm 3+ in the orange–red region by excitation wavelength at 400 nm. The decay time curve of 4 G5/2  →  6 H7/2 transition has been also registered and fitted to a single exponential function.